2001
DOI: 10.1136/heart.85.4.424
|View full text |Cite
|
Sign up to set email alerts
|

Class IC antiarrhythmic drug induced atrial flutter: electrocardiographic and electrophysiological findings and their importance for long term outcome after right atrial isthmus ablation

Abstract: Objective-To describe the electrocardiographic and electrophysiological findings of new atrial flutter developing in patients taking class IC antiarrhythmic drugs for recurrent atrial fibrillation, and to report the long term results of right atrial isthmus ablation in relation to the ECG pattern of spontaneous atrial flutter. Design-Retrospective analysis. Setting-Tertiary care academic hospital. Patients-24 consecutive patients with atrial fibrillation (age 54 (12) years; 5 female, 19 male) developing atrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 13 publications
0
31
0
3
Order By: Relevance
“…4,[20][21][22][23] However, proarrhythmic effects, particularly in patients with ischemic heart disease, and poor long-term sinus rhythm maintenance limit their clinical use. 4,[24][25][26][27][28] Similarly, KCBs such as dofetilide and ibutilide are moderately efficacious anti-AF drugs. 29 Unfortunately, the risk of QT prolongation and ventricular tachyarrhythmias associated with KCBs, particularly in the setting of bradycardia or hypokalemia, are major limiting factors.…”
Section: Discussionmentioning
confidence: 99%
“…4,[20][21][22][23] However, proarrhythmic effects, particularly in patients with ischemic heart disease, and poor long-term sinus rhythm maintenance limit their clinical use. 4,[24][25][26][27][28] Similarly, KCBs such as dofetilide and ibutilide are moderately efficacious anti-AF drugs. 29 Unfortunately, the risk of QT prolongation and ventricular tachyarrhythmias associated with KCBs, particularly in the setting of bradycardia or hypokalemia, are major limiting factors.…”
Section: Discussionmentioning
confidence: 99%
“…It has mild negative inotropic effects and, like propafenone, is associated with a significant incidence of atrial flutter. 15,16 Dizziness and visual disturbance represent the common noncardiovascular side effects seen in 5% to 10% of patients taking flecainide. 17 Propafenone has ␤ blocking in addition to sodium channel blocking activity.…”
Section: Currently Available Antiarrhythmic Drugsmentioning
confidence: 99%
“…It is renally cleared and is prescribed twice daily unless the creatinine clearance is between 30 and 60 mL/min, in which case it should be dosed daily. 16 The usual dose range is 160 to 480 mg/d in divided dosages. It is generally started at a dose of 80 mg twice daily and uptitrated with attention to QT prolongation.…”
Section: Currently Available Antiarrhythmic Drugsmentioning
confidence: 99%
“…9 -11 In this subset of patients with both AF and AFL, CTI ablation and continuation of antiarrhythmic drugs (AADs) has been reported to achieve successful control of both arrhythmias and is still considered an effective and acceptable treatment approach. [12][13][14] Recently, however, it has been demonstrated that in patients with clinical evidence of both AF and typical AFL, AF is induced by triggers from pulmonary vein (PV) foci in Ͼ85% of cases. 15, 16 Kumagai et al 16 suggested that focal activation originating from the PVs may trigger AFL and concluded that CTI ablation combined with PV isolation should be considered in such patients.…”
mentioning
confidence: 99%